2016
DOI: 10.1002/jsfa.7696
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically induced changes in bound phenolics and antioxidants, DNA/cytoprotective potentials in pectic poly/oligosaccharides of tomato (Solanum lycopersicum)

Abstract: This study, for the first time, showed changes in bioactivity profiling in unripened and ripened conditions in tomato. Precise alterations in biomolecular components, such as bound cinnamyl/ferulyl and vanillic acid derivatives, along with alterations in sugar composition that reflect changes in antioxidants, cyto/DNA protective and antimetastatic potentials, have been delineated. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(77 reference statements)
2
8
0
Order By: Relevance
“…Data also showed that Hydnum repandum, Cantharellus clavatus , Lactarius sanguifluus , Sparassis crispa , and Lentius sajor‐caju species also exhibited potent DNA protection, though they contain only moderate levels of antioxidant properties, suggesting that the DNA protective ability of polyphenolic antioxidants need not be due to antioxidative potential but rather could be offering hindrances for free radicals to attach to the DNA molecule. Results support our previous observation, where vanillic acid (VA) and cinnamic acid (CA), having poorer antioxidant potential, exhibited potent DNA protective properties as evidenced by their stronger binding abilities to DNA or proteins 18,27,28 . The current study thus highlights that, as per overall indexing, Termitomyces heimii , Boletus edulis , and Termitomyces mummiformis may be considered as good sources for tyrosinase, antioxidant, and DNA protective potential.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Data also showed that Hydnum repandum, Cantharellus clavatus , Lactarius sanguifluus , Sparassis crispa , and Lentius sajor‐caju species also exhibited potent DNA protection, though they contain only moderate levels of antioxidant properties, suggesting that the DNA protective ability of polyphenolic antioxidants need not be due to antioxidative potential but rather could be offering hindrances for free radicals to attach to the DNA molecule. Results support our previous observation, where vanillic acid (VA) and cinnamic acid (CA), having poorer antioxidant potential, exhibited potent DNA protective properties as evidenced by their stronger binding abilities to DNA or proteins 18,27,28 . The current study thus highlights that, as per overall indexing, Termitomyces heimii , Boletus edulis , and Termitomyces mummiformis may be considered as good sources for tyrosinase, antioxidant, and DNA protective potential.…”
Section: Discussionsupporting
confidence: 89%
“…DNA protective abilities of different mushroom species were determined electrophoretically using calf thymus DNA on DNA agarose gel 18 . Calf thymus DNA and mushroom extracts (5 μg) were incubated at 37°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Erythrocytes are highly susceptible to attack by reactive oxygen species because of the high amount of polyunsaturated fatty acid content in their membranes and the metal catalyzed oxidation reactions mediated by Fe present in haemoglobin [20] . Hydrogen peroxide generated during the autoxidation of oxyhemoglobin contributes to heme degradation leading to the damage of erythrocytes, which in turn leads to change in whole red blood cell structural conformation and its functioning [18] , [19] , [2] , [10] , [11] , [14] .…”
Section: Resultsmentioning
confidence: 99%
“…Whereas NaOH is widely used in the alkali method, , for instance, the BPs (vanillic, ferulic, p -coumaric, caffeic, syringic, chlorogenic acids, etc.) were successfully extracted from both pectic polysaccharides and pectic oligosaccharides of tomato by 1 M NaOH . Besides, KOH has been also employed to decompose the cell-wall structure .…”
Section: Extraction Methods For Bound Phenolicsmentioning
confidence: 99%
“…were successfully extracted from both pectic polysaccharides and pectic oligosaccharides of tomato by 1 M NaOH. 49 Besides, KOH has been also employed to decompose the cell-wall structure. 50 The alkali method, however, requires a pretreatment process that is rather complex.…”
Section: Extraction Methods For Bound Phenolicsmentioning
confidence: 99%